HNF4G increases cisplatin resistance in lung adenocarcinoma via the MAPK6/Akt pathway - Jiaqi Liang; Guangyin Zhao; Yunyi Bian; Guoshu Bi; Qihai Sui; Huan Zhang; Haochun Shi; Guangyao Shan; Yiwei Huang; Zhencong Chen; Lin Wang; Cheng Zhan (PeerJ, 2023)
Background Lung adenocarcinoma is one of the most common tumors, and cisplatin is frequently used in treating lung adenocarcinoma patients. This study aimed to look into the roles and mechanisms of HNF4G in cisplatin resistance of lung adenocarcinoma. Materials & Methods Cisplatin resistance and gene expression data of 542 cell lines from the CTRP and CCLE databases were analyzed. HNF4G expression was detected in the lung adenocarcinoma cell lines after treatment with various concentrations of cisplatin. Cisplatin sensitivity curves were detected in cells that overexpressed or knocked down HNF4G. The ChIP-Seq data were then analyzed to identify the targets of HNF4G involved in cisplatin resistance. Expression and phosphorylation of the MAPK6/Akt pathway were detected after HNF4G was overexpressed or knocked down. Finally, ChIP-qPCR and dual-luciferase assays were used to investigate the regulation of HNF4G on MAPK6. Results In cell lines, high expression of HNF4G was significantly positively correlated with cisplatin resistance, and lung adenocarcinoma patients who had high HNF4G expression had a poor prognosis. Cisplatin treatment increased HNF4G expression, and overexpression of HNF4G significantly increased the resistance to cisplatin in A549 and HCC827 cells, whereas knockdown of HNF4G had the opposite effect. HNF4G overexpression increased MAPK6 expression and activated the MAPK6/Akt pathway, while an Akt inhibitor reduced the effects of HNF4G on cisplatin resistance. HNF4G bound to the MAPK6 promoter region, promoting MAPK6 expression, according to ChIP-qPCR and luciferase assays. Conclusion By binding to the MAPK6 promoter region, HNF4G promotes MAPK6 expression and subsequent Akt phosphorylation, resulting in resistance to cisplatin in lung adenocarcinoma.